Treatment outcomes and plasma level of ritonavir-boosted lopinavir monotherapy among HIV-infected patients who had NRTI and NNRTI failure - Nilkamhang Samruay; Thongyen Supeda; Prasithsirikul Wisit; Amornnimit Wannarat; Kiertiburanakul Sasisopin; Manosuthi Weerawat; Ruxrungtham Kiat; Sungkanuparph Somnuek (AIDS Research and Therapy, 2009)
Abstract Background Different strategies of ritonavir-boosted lopinavir monotherapy have been explored; however, data regarding salvage therapy among HIV-infected patients who failed nucleoside reverse transcriptase inhibitor (NRTI) and non-nucleoside reverse transcriptase inhibitor (NNRTI) is still limited. Methods A prospective study was conducted among HIV-infected patients who failed NNRTI-based antiretroviral therapy with M184V, TAMs, and NNRTI mutations, and were naïve to protease inhibitor. LPV/r at 400/100 mg and lamivudine 150 mg were given twice daily. CD4 and HIV-1 RNA were monitored at week 0, 12, 24, and 48. LPV Cmin was assayed for the first 14 patients using HPLC. Results There were 40 patients with a mean age of 37 years and 70% were male. Median (IQR) baseline CD4 was 123 (37-245) cells/mm3 and median (IQR) HIV-1 RNA was 55,800 (9,670-100,000) copies/mL. By intend-to-treat analysis, 30 (75%) and 24 (60%) patients achieved HIV-1 RNA at <400 and <50 copies/mL, respectively. In as-treated analysis, the corresponding rates were 29 (83%) and 23 (67%), respectively. Low-level viral rebound was found in 6 (15%) patients at week 48. Medians CD4 at week 12, 24, 36 and 48 were 249, 283, 307, and 351 cells/mm3 and significantly changed from baseline (all, P < 0.05). At 6 and 12 weeks, median (min-max) LPV Cmin was 6.52 (1.62-11.64) mg/L and 5.79 (0.75-16.31) mg/L, respectively. There were increments of mean total cholesterol and triglyceride at 48 weeks from baseline (P < 0.05). Conclusion LPV/r monotherapy with recycled lamivudine can maintain virological suppression in a substantial proportion of patients failing NNRTI-based regimen and provides adequate plasma concentrations of LPV although the incidence of low-level viremia is relatively high.